The Effectiveness of Learning Tools: Improving Students’ Scientific Literacy through Collaborative Learning - Virlya Citra Dewi; Endang Susantini; Sri Poedjiastoeti (Universitas Negeri Makassar, 2021)
Scientific literacy is one of the skills that can meet all of the twenty-first century's educational demands. Educators are still struggling to find appropriate instructional tools for teaching these skills. Collaborative learning is considered a suitable model to train students' scientific literacy skills because collaborative activities can encourage students to be active in learning activities. The purpose of this research is to determine how effective learning tools based on collaborative learning are in improving high school students' scientific literacy skills in ecosystem materials. The type of research used is descriptive quantitative research with one group pretest-posttest research design. This study involved 30 students of X graders in Senior High School 1 Ngunut. The N gain score, paired sample t-test, and a sensitivity test are used to determine the learning tools' efficacy. Science skills exam questions are provided in 12 essay questions and are developed using scientific literacy indicators. The results showed an increase in the value of the science literacy skills test with an N gain value of 0.67, the sig value below 0.000, and a sensitivity of 0.48 The final result shows that collaborative learning are effectively used to improve students' scientific literacy skills.